Hubungan Pola Patah Tulang dengan Gejala Klinis pada Patah Tulang Dasar Kepala (PTDK) Anterior - Hardianto Musu; Eko Prasetyo; Maximilian C. Oley; Fredrik G. Langi (Medical Scope Journal, 2024)
Abstract: Traumatic brain injury can occur due to skull base fracture at the anterior, middle, and posterior parts with life-threatening complications. This study aimed to obtain the relationship between anterior skull base fracture pattern and its clinical signs and symptoms. This was a retrospective chart review with a cross-sectional design. Subjects were 50 patients with anterior skull base fracture based on 3D CT scan, and then their clinical signs and symptoms were evaluated. Data were analyzed bivariately using the Pearson Chi-Square test and the Fisher Exact alternative. The results showed that the most common clinical signs and symptoms in type I was anosmia; in type II, related to eyes; in type III, rhinorrhea; and in type IV, signs and symptoms of all entities. The most common fracture pattern in the subjects was frontolateral type (type III). There was a significant relationship between the pattern of fracture based on the 3D CT scan with the clinical signs and symptoms of  patients including cerebrospinal fluid rhinorrhea, anosmia, racoon eyes, and visual deficit (p<0.001). In conclusion, there is a signifinat relationship between pattern of anterior skull base fracture with clinical signs and symptoms. Keywords: traumatic brain injury; anterior skull base fracture; 3D CT scan; clinical signs and symptoms   Abstrak: Cedera otak akibat trauma (COT) dapat terjadi akibat patah tulang dasar kepala (PTDK) baik pada basis tengkorak anterior, tengah, dan posterior, dengan komplikasi mengancam jiwa. Penelitian ini bertujuan untuk mendapatkan hubungan pola patah tulang dengan gejala klinis pada PTDK anterior. Jenis penelitian ialah retrospektif menggunakan rekam medis dengan desain potong lintang. Subjek penelitian ialah 50 pasien PTDK anterior dengan pola patah tulang sesuai 3D CT scan dan dievaluasi kondisi klinisnya. Uji bivariat menggunakan uji Pearson chi-square dengan alternatif Fisher exact. Hasil penelitian mendapatkan gejala klinis yang paling umum: tipe I yaitu anosmia; tipe II yaitu gejala berhubungan dengan mata; tipe III yaitu rinorea; dan tipe IV memberikan gejala yang mencakup semua entitas. Pola patah tulang terbanyak ialah patah tulang frontolateral (tipe III). Pola patah tulang yang dinilai melalui 3D CT-scan berhubungan bermakna dengan derajat gejala klinis pasien PTDK anterior meliputi rinorea cairan serebrospinal, anosmia, racoon eyes, dan defisit visual (p<0,001). Simpulan penelitian ini ialah terdapat hubungan bermakna antara pola PTDK anterior dengan gejala klinis. Kata kunci: cedera otak akibat trauma; patah tulang dasar kepala anterior; 3D CT scan; gejala klinis